1999
DOI: 10.1103/physrevlett.82.4300
|View full text |Cite
|
Sign up to set email alerts
|

C63uNQR Measurement of Stripe Order Parameter inLa2

Abstract: We demonstrate that one can measure the charge-stripe order parameter in the hole-doped CuO2 planes of La1.875Ba0.125CuO4, La1.48Nd0.4Sr0.12CuO4 and La1.68Eu0.2Sr0.12CuO4 utilizing the wipeout effects of 63 Cu NQR. Application of the same approach to La2−xSrxCuO4 reveals the presence of similar stripe order for the entire underdoped superconducting regime The mechanism of high T c superconductivity has been a major controversy throughout the past decade [1][2][3]. The complexity of the phase diagram for temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
255
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(290 citation statements)
references
References 37 publications
35
255
0
Order By: Relevance
“…The frequency dependence of the real and imaginary part of the susceptibility as well as their absolute values are indicative of the cluster glass behaviour similarly as reported by Ghivelder et al The situation may be similar to that observed in the lanthanum cuprates, where slowing down of the spin and/or charge fluctuations results in a strong peak in the spinlattice relaxation for the La nuclei and in a loss of signal on the Cu nuclei and it is ascribed to the glassy magnetic state [23][24][25]. It is interesting that for both Cu and La signals stretched exponential like spin-echo decay is observed in the slow fluctuation limit similarly to the one for FMI signals in manganites, while in the motionally narrowed limit, below a transition temperature T charge , corresponding to the localization of charge-ordered stripes, a Lorentzian single-exponential spin-echo decay is detected [24,26,27]. …”
Section: Resultsmentioning
confidence: 85%
“…The frequency dependence of the real and imaginary part of the susceptibility as well as their absolute values are indicative of the cluster glass behaviour similarly as reported by Ghivelder et al The situation may be similar to that observed in the lanthanum cuprates, where slowing down of the spin and/or charge fluctuations results in a strong peak in the spinlattice relaxation for the La nuclei and in a loss of signal on the Cu nuclei and it is ascribed to the glassy magnetic state [23][24][25]. It is interesting that for both Cu and La signals stretched exponential like spin-echo decay is observed in the slow fluctuation limit similarly to the one for FMI signals in manganites, while in the motionally narrowed limit, below a transition temperature T charge , corresponding to the localization of charge-ordered stripes, a Lorentzian single-exponential spin-echo decay is detected [24,26,27]. …”
Section: Resultsmentioning
confidence: 85%
“…Since 17 O and 63,65 Cu NMR signals undergo a significant wipeout below ∼50 K [19,32], it is difficult to know whether the inhomogeneity probed in 139 La T 1 measurements below ∼60 K is distinct from the one probed at higher temperatures and attributed to spatial variation of the hole concentration. At any given temperature below ∼20 K, the difference in 139 T −1 1 values between x = 0.12 and x = 0.10 samples exceeds an order of magnitude.…”
Section: Inhomogeneity Of the Spin Dynamicsmentioning
confidence: 99%
“…There is clear evidence for charge stripe [2] formation in SC La 1.6-x Nd 0.4 Sr x CuO 4 (Nd-doped LSCO) [3][4][5][6] and YBCO [7][8][9][10]. There are also strong indications that stripes exist in SC Bi2212 [11,12].…”
Section: Introductionmentioning
confidence: 90%
“…Thus, if measurements in cuprates show the presence of quasi-1D charge stripes [3][4][5][6][7][8][9][10][11][12][13], it is absolutely logic to compare transport properties of cuprates with similar properties of quasi-1D metals. Most of the non-CDW quasi-1D metals are organic.…”
Section: Introductionmentioning
confidence: 99%